Wilson's ghost : reducing the risk of conflict, killing, and catastrophe in the 21st century - McNamara, Robert S., 1916-2009.; Blight, James G. (New York : Public Affairs, 2001)
Woodrow Wilson's vision of a collective international action to resist aggressive conflict after the carnage of World War I failed tragically. Over 160 million people died in war during the 20th century, and in Wilson's Ghost, Robert S. McNamara and James G. Blight put forth a decisive, multi-faceted action program for realizing Wilson's dream during this century. The plan begins with a moral imperative that establishes as a major goal of foreign policy across the globe the avoidance of war. To that end, enforcement entails only multilateral intervention on the part of the United States; full reconciliation with Russia and China to integrate those nations into relations with the other Great Powers; restructuring the United Nations to greater effectiveness; defining and deterring war crimes; creating UN enforcement; and finally, reducing nuclear danger by eliminating the huge arsenal held by the United States and Russia, and by signing into law the Comprehensive Test Ban Treaty. The authors support their plan with specific, achievable steps that can begin now to ensure a more peaceful 21st century.
A 21st-century manifesto : choose life over death -- Prologue : Wilson's tragedy, and ours -- A radical agenda : the U.S. role in global security in the 21st century -- Preventing great power conflict : bringing Russia and China in from the cold -- Reducing communal killing : intervention in "dangerous, troubled, failed, murderous states" -- Avoiding nuclear catastrophe : moving steadily and safely to a nuclear-weapons-free world -- Reducing human carnage : an agenda for the 21st century -- Epilogue : Listening to Wilson's ghost.
Includes bibliographical references (p. [231]-252) and index.
Keywords: Peaceful change (International relations); Security, International; Pacific settlement of international disputes; Disarmament; United States -- Foreign relations -- 1989-